Analysis of the Form and Structure of the Song Dealova by Opick - Yulia Erwina; Yensharti (EDUMUSIKA, 2023)
This study aims to describe the form and structure of Opick's Dealova song which consists of rhythm/rhythm, melody, motif, phrase, and period. This type of qualitative research with content analysis approach that is systematic, objectivity, and generalization. The research instrument is the researcher himself. Data were collected through literature study, observation, labor and documentation. Data analysis goes through the procedure of recording observations and labor work, collecting, sorting, finding patterns and relationships which ultimately make findings.Based on the results of the analysis, it was found that the song Dealova by Opick is a popular religious song, created in 1999, although it is religious but the song was used as a sound track for a film with the title Dealova in 2005. This song received an award in 2006 sung by Once. The rhythm of the song uses a time signature of 6/8 with a total of 98 bars. The melody of Dealova's song is more dominantly syllabic and slightly melismatic. In terms of form, Dealova's song includes a three-part song with sentences A, B and C, and undergoes modulation/change of basic tone from E Minor to D minor or from the use of key signature key signature of 1 sharp to 1 mol.